Pension scheme in Singapore: case study and implications - Asher, Mukul G. (1999)
Recent pension reform literature has appropriately stressed the importance of mandatory pre-funding as an important element in ensuring socially adequate, secure, and sustainable retirement financing. This paper, based on an analysis of Singapore's experience, offers several suggestions for economies contemplating a move from non-contributory to contributory fully funded schemes. While pre-funding of retirement financing is desirabale, to ensure intended results, it is essential to give considerable attention to design, implementation, and regulatory issues. In particular, great care needs to be exercised in undertaking the investment of accumulated funds in a prudent, yet remunerative manner. - Reproduced
Keywords: Case studies; Pensions - Singapore; Pensions